Microbiological profile of distinct virulence of Nocardia cyriacigeorgica strains in vivo and in vitro. (May 2020) - Han, Lichao; Ji, Xingzhao; Xu, Shuai; Fan, Shihong; Wang, Chengling; Wei, Kongjiao; Wang, Xuebing; Song, Han; Zheng, Ningwei; Sun, Lina; Qiu, Xiaotong; Hou, Xuexin; et al.
Abstract: There are significant differences between different Nocardia species regarding geographical distribution, biochemical features, phenotypic characterization, and drug sensitivity. In this study, we explored the differences in virulence and pathogenic mechanisms of two Nocardia cyriacigeorgica strains. We examined the difference in virulence between N. cyriacigeorgica ATCC14759 and N. cyriacigeorgica GUH-2 by measuring cytotoxicity, animal survival after infection, the ability of host cell invasion, and viability in host cells. Western blotting was used to compare the differences in activation of MAPKs, including p38, ERK, and JNK, the NF-κB signaling pathway, and the PI3K/Akt signaling pathway in A549 and RAW264.7 cells. We measured the difference in stimulatory effects on production of the cytokines IL-6, IL-10, and TNF-α by ELISA. We found that N. cyriacigeorgica ATCC14759 causes higher cytotoxicity in cultured cells and higher lethality in mice, and exhibits superior invasion ability and viability in host cells compared with N. cyriacigeorgica GUH-2. Moreover, these two strains show marked differences in activation of the expression of cytokines and signaling pathways. N. cyriacigeorgica ATCC14759 is more virulent than N. cyriacigeorgica GUH-2. Furthermore, there is a significant difference in pathogenesis between the two strains. Our results provide a theoretical basis for the prevention and treatment of Nocardia infection. Highlights: The virulence of Nocardia cyriacigeorgica ATCC14759 is higher than that of Nocardia cyriacigeorgica GUH-2. These two strains can activate the MAPK signaling pathway through the phosphorylation of different kinases. These two strains show marked differences in activation of the PI3K/Akt signaling pathways.